No bugs! - Gilholm, W. S.; Sulzer, Anne (Macmillan Education Australia South Yarra, 1998)
"No Bugs!" is a lighthearted children's book about a young character's imaginative journey to rid their world of bugs. Whether they're scared of creepy crawlers or just find them annoying, the protagonist devises clever and sometimes humorous methods to keep bugs away. However, as the story unfolds, they come to realize that bugs play an important role in nature, helping plants grow and keeping the environment balanced. The book delivers a fun, engaging message about the importance of all creatures, even the smallest, in the ecosystem.